Resolving the paradox of bootleg innovation: the role of organizational error management climate in shaping innovation among new-generation employees - Zhao, Bingqian; Hu, Xiushen; Zhang, Zimeng; Guo, Yingying (Frontiers in Psychology, 2025)
IntroductionBootleg innovation is prevalent among new-generation employees, but the influence of organizational error tolerance remains underexplored.MethodsTwo studies were conducted—a three-wave field survey (n = 387) and a scenario-based experiment (n = 200)—to test the proposed model.ResultsError management climate positively predicts bootleg innovation via psychological safety. Promotion focus strengthens this mediation, while defensive focus weakens it.DiscussionThe findings highlight how organizational climate and individual motivation interact to shape constructive deviant innovation.